Evaluation of user embracement software with pediatric risk classification - Gilvan Ferreira Felipe; Francisca Elisangela Teixeira Lima; Lorena Pinheiro Barbosa; Thereza Maria Magalhães Moreira; Emanuella Silva Joventino; Vanessa Sousa Freire; Larissa Bento de Araújo Mendonça (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to evaluate functional performance and technical quality of user embracement software with pediatric risk classification. Method: descriptive exploratory study developed based on the quality requirements set forth in ISO/IEC 25010. The evaluated characteristics were: functional adequacy, reliability, usability, performance efficiency, compatibility, safety, maintainability and portability. Eight specialists from the area of informatics and 13 from nursing participated in the evaluation. The characteristics were considered adequate when they reached more than 70% of indication as very and/or completely appropriate in the evaluations of each group of specialists. Results: The results obtained from the evaluation of informatics and nursing specialists were: functional adequacy (100.0%, 96.2%), reliability (82.6%, 88.5%), usability (84.9%; 98.7%), performance efficiency (93.4%; 96.2%), compatibility (85.0%, 98.1%), safety (91.7%, 100.0%), and, yet, maintainability (95.0%) and portability (87.5%) evaluated by the first ones. Conclusion: the software was considered adequate regarding technical quality and functional performance.